The V(H )gene repertoire of splenic B cells and somatic hypermutation in systemic lupus erythematosus - Fraser, Nicola LW (BioMed Central, 2003)
In systemic lupus erythematosus (SLE) it has been hypothesized that self-reactive B cells arise from virgin B cells that express low-affinity, nonpathogenic germline V genes that are cross-reactive for self and microbial antigens, which convert to high-affinity autoantibodies via somatic hypermutation. The aim of the present study was to determine whether the V(H )family repertoire and pattern of somatic hypermutation in germinal centre (GC) B cells deviates from normal in SLE. Rearranged immunoglobulin V(H )genes were cloned and sequenced from GCs of a SLE patient's spleen. From these data the GC V gene repertoire and the pattern of somatic mutation during the proliferation of B-cell clones were determined. The results highlighted a bias in V(H)5 gene family usage, previously unreported in SLE, and under-representation of the V(H)1 family, which is expressed in 20–30% of IgM(+ )B cells of healthy adults and confirmed a defect in negative selection. This is the first study of the splenic GC response in human SLE.